A Tale of Three Cities - Lynch, John. author. aut Link
IX, 237 p.
Keywords: The city of Belfast tends to be discussed in terms of its distinctiveness from the rest of Ireland, an industrial city in an agricultural country. However, when compared with another 'British' industrial port such as Bristol it is the similarities rather than the differences that are surprising. When these cities are compared with Dublin, the contrasts become even more painfully evident. This book seeks to explore these contrasting urban centres at the start of the twentieth century.